Pengaruh Thin Capitalization, Transfer Pricing Aggresiveness, Multinationality, Besaran Aset Tak Berwujud Dan Pemilihan Auditor Terhadap Penghindaran Pajak Pada Perusahaan Indeks Idxnoncyc - Muhammad Yasykur Aminullah; Murtanto Murtanto; Aqamal Haq (Pusat Riset dan Inovasi Nasional, 2024)
Indonesia is one of the developing countries in the Southeast Asia region and is known as a country with abundant natural resources. The results of this natural wealth stretch from Sabang to Merauke which makes Indonesia. Apart from that, based on Indonesia's geographical location, which is flanked by two continents, namely the Asian continent and the Australian continent, and flanked by two oceans, namely the Indian Ocean and the Pacific Ocean, making Indonesia the world's maritime axis. Due to Indonesia's strategic geographical location, it is not surprising that Indonesia is one of the countries visited by many other countries, whether just for traveling or to start various companies. The number of foreign companies established in Indonesia continues to increase. The conditions are certainly beneficial for the country because it can reduce unemployment and increase the amount of state income in the internal and external sectors. One of the internal revenues for the Indonesian state is through taxes.